The concentration of the creative sector firms as a potential basis for the formation of creative clusters in Poland - Środa-Murawska Stefania; Szymańska Daniela (Bulletin of Geography. Socio-Economic Series, 2013)
The study aims to present the structure and analyse the distribution of economic activities comprising the creative sector (covering 10 sections of PKD 2007 - the Polish Classification of Activities based on NACE rev. 2 - the Statistical Classification of Economic Activities in the European Community) of the Polish economy in the context of the potential basis for the formation of creative clusters in Poland. The study concentrates on the numbers of creative firms based in all 3,076 Polish gminas (306 urban gminas, 1,576 rural gminas and 597 urban-rural gminas; in the latter, 597 urban areas and 597 rural areas are considered separately). As found, most of the firms are involved in architectural and engineering activities; technical testing and analysis (M 71) and other professional, scientific and technical activities (M 74). It has also been established that some local incubators of the potential clusters of creative industries form eight distinct centres, the most prominent of which is the Warszawa centre. The identification of areas with higher concentrations of creative firms has demonstrated that in Poland, like in western countries, creative firms tend to locate in large cities (Warszawa, Kraków, Poznań, Wrocław and Tri-City) and in the regions around them.